2014
DOI: 10.3233/prm-140300
|View full text |Cite
|
Sign up to set email alerts
|

Facial paralysis reconstruction in children and adolescents with central nervous system tumors

Abstract: Facial paralysis remains a vexing problem in the treatment of posterior cranial fossa tumors in children. Fortunately, current techniques are available to reconstruct the paralyzed face in restoring balance, symmetry, and amelioration of functional sequelae. The restoration of structure and function of the paralyzed face is tantamount to proper social integration and psychosocial rehabilitation. In addition, the facial nerve is important in preventing drying of the eyes, drooling, and speech abnormalities, amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 80 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…The combination of HFT and MFT brings together the best of both techniques with good facial resting tone provided by the hypoglossal nerve and wider smile reanimation provided by the masseteric nerve. 2 , 11 Performing the dual nerve transfer bilateral reanimation surgery gives the opportunity of a balanced symmetry of the face both at rest and with movement due to a similar time for recovery in each neurorrhaphy. Having the same donor inputs in each hemiface lessens the possibility of right-left discrepancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of HFT and MFT brings together the best of both techniques with good facial resting tone provided by the hypoglossal nerve and wider smile reanimation provided by the masseteric nerve. 2 , 11 Performing the dual nerve transfer bilateral reanimation surgery gives the opportunity of a balanced symmetry of the face both at rest and with movement due to a similar time for recovery in each neurorrhaphy. Having the same donor inputs in each hemiface lessens the possibility of right-left discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Specifically, posterior fossa tumors imply a high risk of neurological deficits, including FP, because of the tumors themselves or their treatment. 2 Surgical treatment, when needed, includes nerve transfers, mainly masseter-to-facial, or muscle transfers, gracilis free flap or temporalis transposition. Deciding on which surgical option depends on the duration of the paralysis and the feasibility of facial muscles.…”
mentioning
confidence: 99%
“…Dynamic facial reanimation involves complex, time consuming procedures performed under general anesthesia, that are not without risks. In patients operated for intracranial tumors in which the injured proximal facial nerve cannot be used for primary reconstruction using interposition nerve grafts, a dynamic reanimation may necessitate the scarification of another cranial nerve, including the trigeminal, accessory, hypoglossal or contralateral facial nerve (1,2). The indication for such an invasive procedure should carefully consider the general condition of the patient, the existing associated disorders as well as the long-term prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Definitive facial nerve injury during neurosurgical procedures for benign or malignant tumors of the posterior and middle cranial fossae, cerebellopontine angle and lateral skull base, is often unavoidable, either due to existing preoperative tumor invasion or compression, or due to the proximity of the nerve, since the most important desiderate is avoiding tumor recurrence (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…To date, no previous study has reported positive effects of physical therapy in adult brain tumor patients. However, a few reports showed that physical therapy may be effective in pediatric brain tumor patients [47]. In general, physical therapy performed in brain tumor patients is also performed in stroke patients [48].…”
Section: Physical Therapymentioning
confidence: 99%